Socio-Pragmatic Variations in Nigerian Gen-Zers’ Digital Communication - Emmanuel Chinonso Eze; Friday Akachukwu Nnaji (PRASASTI: Journal of Linguistics, 2026)
This study explored the socio-pragmatic variation in the digital communication of Nigerian Generation Z, with a focus on public interactions on Facebook. Drawing on a corpus of naturally occurring posts and comments, the study identified and analyzed emerging linguistic practices, including slangs, acronyms, neologisms, and code-mixing. Grounded in William Labov’s Sociolinguistic Theory of Language Variation (Labov, 1966), the analysis revealed how these forms serve interactional functions, including identity construction, solidarity, humor, resistance, and stance-taking. The findings highlighted Gen Z’s creative adaptation of linguistic resources in response to digital affordances and sociocultural contexts. This research contributed to emerging scholarship in digital discourse, pragmatics, and youth language, and advocated for further study on localized digital vernaculars in multilingual contexts like Nigeria.